Quintuple Helix dan Model Desa Inovatif (Studi Kasus Inovasi Desa di Desa Panggungharjo, Yogyakarta): Quintuple Helix and Innovative Village Model (A Case Study of Village Innovation in Panggungharjo Village, Yogyakarta) - Prasetyanti, Retnayu; Kusuma, Bayu Mitra A. (Jurnal Borneo Administrator, 2020)
Innovation determines the future of village development. This qualitative case study presents an analysis of village governance best practices in economic, environmental, socio-cultural, and technological aspects. Unlike the majority of villages that duplicate innovation, Panggungharjo was able to develop a genuine innovation through the creation of a village-owned enterprise (BUMDes). This scientific paper concludes that participation and synergy among helixes/subsystems in the quintuple helix innovation model (government, industry, universities, civil society, and the natural environment) determine the success of continuing village innovation. In Panggungharjo village, there were 3 affecting factors in succeeding innovation, there were political and leadership capacity; process and bureaucratic capacity; and social and environmental capacity. The use of the top-down & bottom-up innovative village model was also crucial. As a lesson learned, this study formulated the stages of developing innovative villages. The figure of the village leader played a crucial role in the process of initiating innovation and optimizing the village bureaucracy politically and administratively. A set of development roadmap referring to the national priority of the village development program was fundamental. It is also urgent to maintain coordination among helixes so that village innovation can embrace the potential of the village and influence people's welfare. Keywords: Quintuple Helix, Innovation Model, Village Innovation, Village Development, Innovative Village Model Abstrak Inovasi menjadi penentu arah kemajuan desa. Studi kasus kualitatif instrumental ini menyajikan analisis best practice tata kelola inovasi desa pada aspek ekonomi, lingkungan, sosial-budaya, dan teknologi. Berbeda dengan sebagian besar desa yang melakukan duplikasi inovasi, Desa Panggungharjo mampu mengembangkan inovasi secara mandiri melalui pembentukan BUMDes, sebuah lembaga ekonomi-sosial desa. Artikel ini menunjukkan bahwa partisipasi dan sinergi antarsubsistem dalam model inovasi quintuple helix (pemerintah, industri, universitas, masyarakat sipil, dan lingkungan alami) menjadi penentu keberhasilan inovasi desa yang berkelanjutan. Terdapat tiga faktor penentu keberhasilan inovasi, mengacu pada istilah Kepala Desa Panggungharjo, didefinisikan sebagai tiga kapasitas (kompetensi) utama, yaitu; (1) kapasitas politik dan kepemimpinan; (2) kapasitas proses dan birokrasi; (3) kapasitas sosial dan lingkungan. Aspek penting lain yang perlu diperhatikan adalah penerapan model desa inovatif berbasis pendekatan top-down & bottom-up. Studi ini merumuskan tahapan pengembangan desa inovatif sebagai lesson learnt dari kesuksesan inovasi di Desa Panggungharjo. Sosok pemimpin desa memegang peran krusial terutama dalam proses inisiasi program inovasi dan optimalisasi birokrasi desa. Pemerintah desa dituntut untuk mampu menyusun roadmap perencanaan pembangunan desa sesuai arah kebijakan/program prioritas desa dalam lingkup nasional. Sebagai tindak lanjut, pengembangan inovasi harus didasarkan pada koordinasi dan penguatan jaringan kerja sama antar-helix sehingga dapat berimbas pada pemerataan kesejahteraan masyarakat. Kata Kunci: Quintuple Helix, Model Inovasi, Inovasi Desa, Pembangunan Desa, Model Desa Inovatif